Design, Heritage e cultura digitale Scenari per il progetto nell'archivio diffuso - Tufarelli, Margherita (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
With the digital transformation, the exponential increase in the number of tools and types of support with which human expressions can be created and transmitted brings with it new cultural paradigms that feed creative productions and vice versa, giving rise to new questions regarding how Heritage "works", what it "does" and what it "serves". This is the general context in which the research project described in this book is set, and the convergence that has been created over time between technologies, cultural heritage, and design, which today seem to implement a triangulation in which each vertex favors the relationship between the other two, opening up new and interesting research perspectives to explore.